Analysis of Disaster Mitigation in IPAS Subject of High School Phases under Merdeka Belajar Concepts - Novita, Mega; Nurohmah, Amin; Ma’arif, Syamsul; Anh Huynh Nguyen, Tam; Kusumo, Haryo; Marlina, Dian; Taufik Anwar, Muhammad (KnE Social Sciences, 2022)
Indonesia’s geographical condition is vulnerable to geological changes and prone to natural disasters. The Indonesian Government has made various efforts to reduce disaster risk by developing disaster-safe education units. Disaster education will be effective if it is integrated into the curriculum in the school subjects such as social studies from an early age. This study aims to provide ideas for implementing disaster mitigation learning for high school students based on the concept of Merdeka belajar in the digital age. To better understand disaster preparedness under the concepts of Merdeka belajar, we thoroughly examined the relevant databases. It was carried out within the education framework put out by Ki Hadjar Dewantara (1889–1959), Johann Friedrich Herbart (1776–1841), and Jan Komensky (1592-1670). Given that Indonesia has at least 13 disaster threats whose risks vary depending on the region, it is crucial to understand the local wisdom in disaster mitigation. This content is available in high school phases’ natural and social sciences subjects (ilmu pengetahuan alam dan sosial, IPAS). This research is crucial to successfully improve the teaching-learning quality to meet the needs of the Pancasila student profile. Keywords: disaster mitigation, IPAS, high school, merdeka belajar, digital learning